Development of a Novel Telemanipulation Framework for Human-robot Collaboration Using PTC ThingWorx and Vuforia Studio - (:unkn) unknown (My University, 2022)
Significant advancements in contemporary telehealth care applications are enforcing the demand for effective and intuitive telerehabilitation tools. The current techniques for observing live process parameters of robots frequently require complex and inefficient methods, which fundamentally limits the human administrator's ability to settle on the most educated decisions possible. Telemanipulation can minimize the distance and costs in varieties of robot applications, including industry for object manipulation and robot-aided rehabilitation. This research aims to develop a novel telemanipulation framework to deliver robot-assisted rehabilitation using PTC ThingWorx’s Industrial Internet of Things (IIoT), and Vuforia Studio’s Augmented Reality (AR) platforms. This communication architecture is stable and has low latency for teleoperation. Our research shows that a remote operator (e.g., a remote therapist) can provide a variety of upper-limb rehab exercises using the developed AR-based graphical user interface (GUI), which transmits bidirectional data between the AR platform and the robot through the ThingWorx IIoT platform. For the kinematic modeling of the robotic manipulator (xArm-5 robot) used in this study, modified Denavit-Hartenberg (DH) parameters were used. The developed AR platform displays the robot data in real-time, such as joint angles, velocity, motor current, etc., thus allowing an operator (e.g., a caregiver/therapist) to monitor the robot motion representing various upper-limb rehabilitation therapies. This research also developed a telemanipulation approach using a physical joystick to teleoperate the xArm-5 robot. The experimental results revealed that the xArm-5 can be teleoperated successfully and effectively using the developed AR platform and a physical joystick to provide upper-limb telerehabilitation therapy.
Keywords: Augmented Reality; IIoT; Telemanipulation; Telerehabilitation; ThingWorx; Upper-limb Rehabilitation